Relationship between knowledge, education, and support of health workers on mosquito nest eradication behavior in Kedaton community health center: A cross-sectional study - Sumantri, Apria Wilinda (Lentera Perawat, 2025)
Background: Dengue fever (DF) remains a major global health problem with a high prevalence in Indonesia. The behavior of mosquito breeding site eradication (known as PSN) is the primary strategy for dengue prevention; however, it is influenced by factors such as knowledge, education, and support from healthcare workers. Objective: This study aimed to analyze the relationship between knowledge, education, and healthcare worker support and mosquito breeding site eradication (PSN) behavior in the working area of UPTD Kedaton Public Health Center in 2025. Methods: A quantitative descriptive study with a cross-sectional approach was employed. The sample consisted of 50 heads of households in RT 01 RW 01, Kedaton Village, selected using a total sampling technique. Data were collected using a structured questionnaire and checklist to assess independent variables (knowledge, education, and healthcare worker support) and the dependent variable (PSN behavior). Data were analyzed using the Chi-Square test with a significance level of 0.05. Results: The majority of respondents demonstrated negative PSN behavior (58%), had poor knowledge (54%), and possessed a low level of education (56%). The Chi-Square test revealed a significant association between knowledge (p = 0.000), education (p = 0.001), and healthcare worker support (p = 0.000) with PSN behavior. Respondents with good knowledge, higher education, and strong support from healthcare workers tended to exhibit positive PSN behavior. Conclusion: Knowledge, education, and healthcare worker support play crucial roles in improving community PSN behavior. Continuous health education interventions and the strengthening of healthcare workers’ roles are essential strategies to reduce dengue incidence in endemic communities.